Cosmopoéticas ribeirinhas: alertas sobre mudanças do tempo e alianças para criações estéticas e políticas com o rio São Francisco - Souza, Leon Patrick Afonso de (2024)
The focus of this research is to understand how the creations - multiple ways of organizing their own experiences politically, creatively and discursively - of fisherwomen, vazanteiros and artists serve as both a warning and resistance to the transformations caused by the installation of colonial, hydroelectric, mining and agricultural enterprises on the São Francisco River, specifically in the area between the municipalities of Buritizeiro and Pirapora, in northern Minas Gerais. In this sense, my first move was to ethnographically record some of the warnings about the setbacks, i.e. profound changes in the course, volume and smell of the waters, which impact the piracema, fish mortality and leave the barranqueiros uncertain about the period for planting and harvesting in the vazantes. By issuing warnings about the transformations between calendar time and climate time, the setback is also enunciated as a denunciation against the occupations that, since colonization, have violated riverside existences. I then tried to show how artists, fisherwomen and vazanteiros forge their alliances based on aesthetic and political creations among the sediments of colonial dwelling on the riverside worlds, prolonging the effect of the struggles beyond the present and the future, because the catastrophe is not just coming, but is underway. Inspired by Dénètem Touam Bona, here I make a theoretical and methodological choice to privilege other meanings, which is why I include the memory and memories I have of my childhood and adolescence, when I went fishing with my father and my mother, and the struggles I took part in with social movements and leaders against hydroelectric projects, fish mortality and for the right to exist of the people and other beings. Engaging with the cosmopoetic proposal has allowed me to develop an ethnography that listens, narrates and recognizes the worlds and multiple existences with the São Francisco, even in the face of setbacks. In the same way, placing myself ethnographically among the riverside cosmopoetics was an opportunity to learn how to resist from the ontological, aesthetic and political creations of the barranqueiro people.